قياس كفاءة البنوك في القطاع المصرفي الجزائري باستخدام تحليل مغلف البيانات DEA - صيفي فوزي (Universty Of El-oued جامعة الوادي, 2024)
الملخص: تهدف الدراسة إلى قياس كفاءة البنوك في القطاع المصرفي الجزائري للفترة (2011-2020) باستخدام الأسلوب اللامعلمي "تحليل مغلف البيانات (DEA)" من خلال عينة تتكون من (15) بنكا عاملا في الجزائر، (6) بنوك عمومية و(9) بنوك خاصة، وطبقت الدراسـة التوجيه الإخراجي بنموذجيه، ثبات الغلة إلى الحجم (CRS-O) وتغير الغلة الى الحجم (VRS-O)، بالاعتماد على الودائع، المصاريف العامة للاستغلال ومخصصات اهتلاك الأصول كمدخلات، والقروض والنتائج البنكي الصافي كمخرجات، وأظهرت نتائج الدراسة أن البنوك الجزائرية محل الدراسة حققت في المتوسط كفاءة تقنية إجمالية (0,761)، كفاءة تقنية صافية (0,832) وكفاءة حجمية (0,915)، وخلصت الدراسة إلى أن البنوك الجزائرية لا تحسن التوليف بين المدخلات لتحقيق أقصى ما يمكن من المخرجات، وأن البنوك الخاصة أفضل كفاءة تقنية من البنوك العمومية، بالإضافة إلى أن البنوك الجزائرية لا تتمتع بالحجم الأمثل، وأن جل هذه البنوك ستواجه صعوبات في توسيع حجم نشاطها لأنها غالبا ما تحقق غلة حجم متناقصة، كما توصلت الدراسة إلى أن سبب عدم تحقيق البنوك لكفاءة تقنية إجمالية غالبا ما كان مرتبطا بالجوانب الفنية والحجمية معا، مع تأثير أكبر للجوانب الفنية، وأهم ما تقدمه الدراسة من توصيات، ضرورة قيام البنوك بالتحسينات المقترحة من أسلوب DEA للتقليل من الهدر في الموارد، وتعزيز مستوى الشفافية والإفصاح في القطاع المصرفي الجزائري. Abstract: The study aims to measure the efficiency of banks in the Algerian banking sector for the period (2011-2020) using the nonparametric method "Analysis of the data envelope (DEA)", through a sample of 15 banks operating in Algeria, 6 public banks and 9 private banks. The study applied the Output-Orient in its two models, constant returns to scale (CRS-O) and variable returns to scale (VRS-O), based on deposits, general operating expenses and asset impairment allowances as inputs, and loans and net banking results as outputs. The results of the study showed that Algerian banks studied during the period (2011-2020) achieved on average overall technical efficiency (0,761) and pure technical efficiency (0,832), and scale efficiency (0,915). The study concluded that most Algerian banks do not improve the combination of inputs to achieve the maximum possible outputs, and that private banks are more technically efficient than public banks. In addition, Algerian banks are not operating at the optimal scale, and most of these banks will find it difficult to increase the volume of their business because they often achieve a Decreasing Return to Scale. The study also finding that the reason for banks' failure to achieve overall technical efficiency is often linked to the technical and scale aspects together, with the technical aspects having a greater influence. The most important recommendations that the study presents are the need for banks to make the improvements proposed by the DEA method to reduce the waste of resources, and enhancing the level of transparency and disclosure in the Algerian banking sector.
دراسة عينة من البنوك للفترة 2011 - 2020
أطروحة دكتوراه تخصص: اقتصاد نقدي وبنكي في العلوم الاقتصادية والتجارية وعلوم التسيير
Keywords: بنوك؛ كفاءة بنكية؛ كفاءة تقنية؛ كفاءة حجمية؛ تحليل مغلف البيانات DEA؛ الجزائر.; Banks; banking efficiency; technical efficiency; scale efficiency; data envelopment analysis DEA; Algeria.